Sculpture et datation, le renouveau d’un enjeu - Christian Sapin (Les Cahiers de l'École du Louvre)
Based on the corpus of fourth-tenth century architecture, the corpus for sculpture of the same period in France that is being prepared includes in its fields the various arguments necessary for the dating of sculpted elements. A combination of archaeology and art history, the dating of sculptures in earlier works was often assessed based on a single criterion, such as historical sources from the site of provenance, or formal or morphological comparisons. The estimation of the age of the capitals at Jouarre, the baptistery of Poitiers and Saint-Laurent de Grenoble was largely based on historical sources. How has this changed, now that archaeology has been able to assess these sites? How can we understand the contemporaneity of Carolingian decoration given the reused elements, replicas and new works, as at Saint-Germain d’Auxerre? It was long thought that the revival of Romanesque sculpture took place after the year 1000. Has the recent study of the frames of numerous buildings from this period been a guarantee of more precise dating through archaeometry or, on the contrary, a calling into question? What about works outside the context of known or studied monuments? All these questions are presented with examples and, we hope, the database of the proposed corpus will provide answers to them through the interaction of crossed criteria.